Group factors influencing the majority of Cameroonian consumers’ attitudes towards counterfeits products - Justin, Lekini Dieudonne´; Fonchamnyo, Dobdinga Cletus; Oad, Salochina; John, Moti Wilson; Naheed, Rehana (Edelweiss Applied Science and Technology, 2022)
Counterfeiting is a serious issue in developing economies, and many authentic marques have fallen victim to it. Counterfeit products deceive consumers and cause an increase in the demand for lower-cost replications, which can devalue authentic products. The paper investigates the influential factors that motivate Cameroonian consumers’ intent to purchase counterfeits. The construction of our model is inspired by the theory of buyer behavior, recognized by several researchers as the most reliable construct. The association between the utility theory and the theory of planned behavior is introduced for the first time in this study. We compute the Pearson correlation Coefficient, calculate the Cronbach alpha, and run Binary Logistic Regressions using a sample of 1,000 Cameroonians (males and females) living or who have lived in China. The findings show that, more than any other element under consideration, economic reasons account for disparities in Cameroonian attitudes towards counterfeit goods. The findings validate the variables’ effects on Cameroonian consumers’ opinions of and intentions to buy counterfeit goods, supporting the stated predictions. Counterfeit sales have grown into a multibillion-dollar industry, and identifying the reasons behind consumers’ motivation and intention to buy counterfeit products rather than original ones can be beneficial to both policymakers and firms. This paper might affect these stakeholders’ thoughts and/or actions towards counterfeits. As a result, they can develop strategies to combat the availability of counterfeit products and interact with Cameroonian consumers.